2019
DOI: 10.1016/j.jtho.2018.12.033
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Air Pollution and Lung Cancer in Nonsmokers in Taiwan

Abstract: Introduction: For never-smokers (smoked <100 lifetime cigarettes), lung cancer (LC) has emerged as an important issue. We aimed to investigate the effects of prevalence changes in tobacco smoking and particulate matter (PM) 2.5 (PM 2.5) levels on LC in Taiwan, in relation to contrasting PM 2.5 levels, between Northern Taiwan (NT) and Southern Taiwan (ST). Methods: We reviewed 371,084 patients with LC to assess smoking prevalence and correlations between the incidence of adenocarcinoma lung cancer (AdLC) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 25 publications
4
102
0
Order By: Relevance
“…Although we found a statistically significant association between air pollution and subsequent SHL, the present study had the following limitations that need to be considered: (1) The noise levels in the studied area and the genetic variants in the studied subjects, which are considered as important risk factors for SHL, were not clarified in the present study, and without the noise-level data, the scope and significance of the study are limited. (2) The study conducted in the assigned residential area was according to the subject's condition which was associated with the treatment of acute upper respiratory infections in a clinic or hospital, resulting in the underestimation of every subject's exposure level to each air pollutant in the studied area. However, our findings are still significant and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we found a statistically significant association between air pollution and subsequent SHL, the present study had the following limitations that need to be considered: (1) The noise levels in the studied area and the genetic variants in the studied subjects, which are considered as important risk factors for SHL, were not clarified in the present study, and without the noise-level data, the scope and significance of the study are limited. (2) The study conducted in the assigned residential area was according to the subject's condition which was associated with the treatment of acute upper respiratory infections in a clinic or hospital, resulting in the underestimation of every subject's exposure level to each air pollutant in the studied area. However, our findings are still significant and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as urbanization, industrialization, heavy traffic, or establishment of thermal power stations, result in air pollution in several countries. Primarily, lung cancer is considered the major severe disease caused by air pollution [1,2]. Notably, accumulating evidence shows that chronic exposure to air pollution is associated with not only respiratory diseases but also non-lung cancers [3,4] and cardiovascular [5,6], inflammatory [7,8], and neurodegenerative diseases [9,10] including age-related macular degeneration (AMD) [11].…”
Section: Introductionmentioning
confidence: 99%
“…LCINS exhibits distinct molecular characteristics, and the incidence of lung cancer in Asian NSFs is particularly high (17,18). In Taiwan, 55% of the lung cancers are in never-smokers, lung cancer is the leading cause of cancer-related death among women, and over 90% of female patients with lung cancer are never-smokers (19). Recently, there has been an interest in LDCT screening for lung cancer among female never-smokers in China, Japan, Korea, and Taiwan (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…In a study published in 2020 in China, it was reported that in the recent ten years, the percentage of lung adenocarcinoma (LUAD) increased signi cantly with a decrease in squamous carcinoma [3]. The increasing incidence of lung adenocarcinoma (LUAD) has also been reported to be associated with air pollution-related factors [4][5][6]. In previous studies, it was reported that PM 2.5 increased the pro-in ammatory lipid metabolism in the lung and was associated with lipid alterations [7,8].…”
Section: Introductionmentioning
confidence: 99%